Seasonality and Relative Abundance of tabanids (Diptera, Tabanidae) on Marambaia Island, Rio de Janeiro, Brazil. - Guimaraes, Ronald Rodrigues; Guimarães Júnior, Ronald Rodrigues; Harlan-Rodrigues, Ronald Storti; Guimarães, Roney Rodrigues; Carvalho, Raimundo Wilson; Xerez, Roberto de (EntomoBrasilis, 2017)
Abstract. Tabanids collections were conducted on Marambaia Island, Atlantic Forest biome, Rio de Janeiro, Brazil. Thirty-one species were identified belonging to 16 genera. Seasonal variation and its relationship with the most important climatic factors during 1981 and 2013 and observations on the bionomics of each species are presented. Variação sazonal e abundância de tabânidas (Diptera, Tabanidae) na Ilha da Marambaia, Rio de Janeiro, Brasil Resumo. Coletas de tabânidas foram realizadas na ilha de Marambaia, bioma da Mata Atlântica, Rio de Janeiro, Brasil. Trinta e uma espécies foram identificadas pertencentes a 16 gêneros. São apresentadas a variação sazonal, observações sobre bionomia e a relação com os fatores climáticos mais importantes durante os anos de 1981 e 2013.